Restaurant wastewater treatment technologies and potential of biofringe fibre - Rashid, Mohamad Amirul Qaiyum; Abduh Algheethi, Adel Ali Saeed; Abdul Kadir, Aeslina; Sarani, Noor Amira (Penerbit UTHM, 2021)
Restaurant industries are one of the pollution sources in the environment, due to the huge quantities of wastewater that was discharged into the public sewers and drains. However, the discharge of this untreated restaurant wastewater into the environment is considered one of the main issues. Nevertheless, other methods can be employed to safely discharge this contaminated wastewater into the environment.